The Perceived External Prestige of University Professors - Assistant Professor Dr. Talib Ali Muttaleb Dhamin (Genius Journals, 2024)
The current research aims to identify: The perceived external prestige (subjective dimension – objective dimension) of university professors. Differences in perceived external prestige (subjective dimension – objective dimension) among university professors according to gender variable (male – female). To achieve this, Hoyle’s (2001) scale of perceived external prestige was adopted from (53) paragraphs of the type of declarative paragraphs, distributed on two separate dimensions (subjective dimension and objective dimension) applied to a sample of university professors who were selected by stratified random method and by equal distribution method. Their number reached (100) male and female teachers after making sure of its psychometric characteristics in terms of validity and reliability. The results showed that university professors have the subjective dimension of perceived external prestige more than the objective dimension, and there are no differences between university teachers of both sexes in the perceived external prestige in both subjective and objective dimensions. To complete the research, the researcher put some recommendations and suggestions.
Keywords: subjective; dimensions; professors